Assuming this a system of equations and you need the solution set, you can solve it by elimination or substitution–whichever you find easier. i’ll use elimination:

2x – 5y = 3
x – 3y = 1

here, it’ll be pretty easy to get your x values to match so you can cancel them out. just multiply your bottom equation by 2, then subtract:

   2x – 5y = 3
– (2x – 6y = 2)
your 2x’s cancel out and -5y + 6y is simply y, so you’re left with:

y = 1

that already gives you your answer, because you can see that the first ordered pair is the only pair with a y-value that’s 1, but still, to check your x-value, you just plug your y-value into one of the equations:

x – 3(1) = 1
x – 3 = 1
x = 4

so your solution is (4, 1).